2020
DOI: 10.1128/msphere.00061-20
|View full text |Cite
|
Sign up to set email alerts
|

ZupT Facilitates Clostridioides difficile Resistance to Host-Mediated Nutritional Immunity

Abstract: Clostridioides difficile is a spore-forming bacterium that causes severe colitis and is a major public health threat. During infection, C. difficile toxin production results in damage to the epithelium and a hyperinflammatory response. The immune response to CDI leads to robust neutrophil infiltration at the sight of infection and the deployment of numerous antimicrobials. One of the most abundant host immune factors associated with CDI is calprotectin, a metal-chelating protein with potent antimicrobial activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…Although AdcAII and Pht‐encoding genes are absent in S. mutans , a gene ( smu2069 ) coding for a hypothetical protein with 37% identity and 60% similarity to the Escherichia coli ZupT, a member of the zinc import ZIP family commonly found in gram‐negative and in selected gram‐positive bacteria (Grass et al., 2002; Zackular et al., 2020), was identified through BLAST searches. To probe the possible role of Smu2069 in zinc uptake, we created a strain bearing a smu2069 deletion in UA159 (Δ smu2069 ) and in the Δ adcCB background thereby generating a Δ adcCB Δ smu2069 triple mutant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although AdcAII and Pht‐encoding genes are absent in S. mutans , a gene ( smu2069 ) coding for a hypothetical protein with 37% identity and 60% similarity to the Escherichia coli ZupT, a member of the zinc import ZIP family commonly found in gram‐negative and in selected gram‐positive bacteria (Grass et al., 2002; Zackular et al., 2020), was identified through BLAST searches. To probe the possible role of Smu2069 in zinc uptake, we created a strain bearing a smu2069 deletion in UA159 (Δ smu2069 ) and in the Δ adcCB background thereby generating a Δ adcCB Δ smu2069 triple mutant.…”
Section: Resultsmentioning
confidence: 99%
“…Growth curves of UA159, ΔadcA, ΔadcCB, or ΔadcCB comp in (a) FMC, (b) FMC supplemented with 5 μM ZnSO 4 , (c) BHI, (d) CP/BHI medium containing 200 μg/ml of human calprotectin, and (e) BHI containing 10 μM TPEN. Curves shown represent average and SD of at least five independent biological replicates [Colour figure can be viewed at wileyonlinelibrary.com]import ZIP family commonly found in gram-negative and in selected gram-positive bacteria(Grass et al, 2002;Zackular et al, 2020), was identified through BLAST searches. To probe the possible role of Smu2069 in zinc uptake, we created a strain bearing a smu2069 deletion in UA159 (Δsmu2069) and in the ΔadcCB background thereby generating a ΔadcCBΔsmu2069 triple mutant.…”
mentioning
confidence: 99%
“…The inflammatory S100 protein calprotectin also contributes to bacterial killing at certain sites of infection by sequestering metals [including Zn(II) and Mn(II)] following its copious release from neutrophils [ 13 ]. Nonetheless many bacterial pathogens can overcome this host mediated metal-limitation via Zn(II) uptake systems (for example [ 14 16 ]), and notably C . jejuni possesses an ATP-binding cassette (ABC) Zn(II)-importer needed for intestinal survival [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…While AdcAII and Pht-encoding genes are absent in S. mutans, a gene (smu2069) coding for a hypothetical protein with 37% identity and 60% similarity to the E.coli ZupT, a member of the zinc import ZIP family commonly found in gram-negative and in selected gram-positive bacteria (Grass, Wong, Rosen, Smith, & Rensing, 2002;Zackular et al, 2020) was identified through BLAST searches. To probe the possible role of Smu2069 in zinc uptake, we created a strain bearing a smu2069 deletion in UA159 (Δsmu2069) and in the Δ adcCB background thereby generating a Δ adcCBΔsmu2069 triple mutant.…”
Section: Adcabc Is the Main Transporter Responsible For Zinc Uptake In S Mutansmentioning
confidence: 99%